A Pelvic Abscess and a Pelvic Stone Secondary to a Ureteral Calculus - Bo-Ran An; Ze-Peng Ma; Chao Gao (Case Reports in Radiology)
The patient presented with abdominal pain for the first time 10 years ago and was diagnosed with a left ureteral calculus, left hydronephrosis, and hydroureter. The patient’s abdominal pain disappeared after palliative treatment, but he refused any treatment measures for his calculus and hydrops. He was readmitted due to chronic pelvic pain 8 years ago and was diagnosed with a pelvic abscess and left renal atrophy after imaging examination. We performed pus aspiration treatment under the guidance of transrectal B-mode ultrasound and used antibiotic fluid for purulent cavity rinse, followed by intravenous injection of antibiotics. The abscess shrank in follow-up magnetic resonance imaging (MRI), and the pain symptom disappeared in his pelvic. We followed up with the patient for 6 months, and he had no symptoms related to his pelvic abscess that was diagnosed before. Recent abdominal computed tomography (CT) images revealed that his left kidney atrophy still exists, and a pelvic stone was found at the site of the original abscess. This case once again proves that a ureteral calculus should be treated in time; otherwise, it can lead to serious complications such as a pelvic abscess and renal atrophy. A pelvic stone can be caused by a ureteral calculus migration. Minimally invasive treatments have minimal damage to the body and are widely applicable, and the patient was cured by one of them, abscess aspiration, which implies that they can also be used for patients who cannot tolerate surgical procedures.